Effects of Pitaya Peel Supplementation on Nutritional Quality, Overall Sensory Acceptance, In Vitro Glycemic Index, and Antioxidant Release from Fiber-Enriched Cookies - Thi Hai Anh Mai; Thi Thu Tra Tran; Van Viet Man Le (Journal of Food Quality)
Pitaya peel is a by-product of fruit processing. In this study, the effects of pitaya peel supplementation in the cookie recipe on the nutritional quality, in vitro glycemic index, and antioxidant release from the enriched fiber cookies were investigated. The higher the ratio of pitaya peel powder (PPP) in the recipe, the greater the dietary fiber, betacyanin and phenolic contents, and antioxidant activities of the product. Cookies supplemented with 10–25% PPP were classified as having a low glycemic index, ranging from 51.9 to 45.7 in relation to glucose reference. The release of betacyanins, phenolics, and antioxidant activities from the cookie samples was recorded at the salivary, gastric, intestinal, and colon steps during in vitro sequential digestion, and the gastric digestion showed the highest release of antioxidant content and activity. The increased PPP ratio in the cookie recipe improved the antioxidant activities of the aqueous fractions at the four digestive steps. Statement. This study has a preprint entitled “Effects of the ratio of pitaya peel powder on the product quality, predicted glycemic index, and antioxidant release during in vitro sequential digestion” (DOI: https://doi.org/10.21203/rs.3.rs-2322871/v1). This preprint was posted on the research square website on December 5th, 2022.